2010
DOI: 10.2174/1874331501004010111
|View full text |Cite
|
Sign up to set email alerts
|

History and Use of Wood Pyrolysis Liquids as Biocide and Plant Protection Product

Abstract: Archeological studies have found that pyrolysis liquids were already used in the time of the Neanderthal. Wood vinegar and other slow pyrolysis liquids are produced as a by-product of charcoal production. However, future business ideas may be the other way round as pyrolysis liquids may replace synthetic chemicals in the form of pesticides and biocides.Directives and regulations related to the sustainable use of pesticides govern and direct plant protection strategies towards a lower use of synthetic chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
107
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 43 publications
0
107
0
11
Order By: Relevance
“…The pyrolysis liquid is obtained as a by-product during the manufacture of charcoal, and it is used extensively in plant growth and protection, particularly in pesticide applications (Tiilikkala et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The pyrolysis liquid is obtained as a by-product during the manufacture of charcoal, and it is used extensively in plant growth and protection, particularly in pesticide applications (Tiilikkala et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Slow pyrolysis occurs at a low heating temperature of 400°C and a long solids residence time causing the secondary cracking of the primary products (Brewer, et al, 2009), (Tiilikkala, et al, 2010). The major product yields include biochar up to 45% and bio-oil (vinegar and tar) about 30% (Baimark and Niamsa, 2009), (Chalermsan and Peerapan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the major components of wood vinegar are acetic acid and methanol while acetone, methyl acetone, acetaldehyde, allyl alcohol, furan and furfural, and formic, propionic and butyric acids among others are also present (Tiilikkala, et al, 2010). On the other hand, wood tar generally consists of aldehydes, ketones, acids, and esters compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also contains various kinds of phenol, carbonyl, and alcohol. In pesticide application, wood vinegar has been widely used as a wood preservative, fungicide, repellent and insecticide, herbicide, and feed-stuff 8 . Yatagai et al 9 was reported that wood vinegar produced from mixed chips of Cryptomeria japonica and …”
Section: Introductionmentioning
confidence: 99%